2019
DOI: 10.1136/bmjgh-2018-001116
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics for Lassa fever virus: a genetically diverse pathogen found in low-resource settings

Abstract: Lassa fever virus (LASV) causes acute viral haemorrhagic fever with symptoms similar to those seen with Ebola virus infections. LASV is endemic to West Africa and is transmitted through contact with excretions of infected Mastomys natalensis rodents and other rodent species. Due to a high fatality rate, lack of treatment options and difficulties with prevention and control, LASV is one of the high-priority pathogens included in the WHO R&D Blueprint. The WHO LASV vaccine strategy relies on availability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 140 publications
(167 reference statements)
2
62
0
1
Order By: Relevance
“…The high level of genetic diversity between LASVs also poses a diagnostic challenge as only <75% of the genome sequence is conserved. Phylogenetic analysis based on whole genome sequencing showed that LASV is grouped into four main lineages 1 2. A fifth ‘AV’ lineage from Mali/Cote D’Ivoire has recently been proposed 12.…”
Section: Challenges In Lasv Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high level of genetic diversity between LASVs also poses a diagnostic challenge as only <75% of the genome sequence is conserved. Phylogenetic analysis based on whole genome sequencing showed that LASV is grouped into four main lineages 1 2. A fifth ‘AV’ lineage from Mali/Cote D’Ivoire has recently been proposed 12.…”
Section: Challenges In Lasv Detectionmentioning
confidence: 99%
“…Despite measures to prevent and control the spread of Lassa virus (LASV), the fight against Lassa fever is hampered by a lack of vaccines, well-documented therapeutics and appropriate diagnostics 1 2. There are currently no commercially available diagnostics capable of capturing the diversity among viral strains and providing a diagnosis at any time-point during the clinical course of illness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LF is also known to be endemic in Benin, Ghana, and Mali [1]. LF disease is an acute viral hemorrhagic disease caused by Lassa Virus (LASV), a bisegmented single-stranded RNA virus, which belongs to the family Arenaviridae [1,6]. The putative reservoir of LASV is the Mastomys natalensis, which is known to exhibit asymptomatic infection but results in copious shedding of the virus in the urine, feces, saliva, and blood of infected rats [1,7].…”
Section: Introductionmentioning
confidence: 99%
“…It is vital that the current lack of rapid diagnostic tests for priority pathogens is addressed, to ensure that future outbreaks can be more effectively contained. Detailed descriptions of the diagnostic landscapes for selected WHO R&D Blueprint pathogens are provided in this supplement 15–19. Each of these pathogens presents specific challenges, due to differences in factors such as geographical location (Nipah infection primarily occurs in Asia, Middle East respiratory syndrome-coronavirus (MERS-CoV) in the Middle East and Lassa fever in Africa, while Crimean-Congo haemorrhagic fever (CCHF) is widespread) and mode of transmission (MERS-CoV in particular has a significant animal reservoir in dromedary camels, while CCHF is a tick-borne disease), among others.…”
Section: Introductionmentioning
confidence: 99%